Influences of various particle sizes of coal bottom ash as supplementary cementitious material on the pozzolanic properties - Al Biajawi, Mohammad I.; Rahimah, Embong; Andri, Kusbiantoro; Aljabbar, Haneen Abd (Springer, 2024)
The development of the world population shows a similar upward trend in the use of cement in the construction sector and rising tendency in the production of cement. These two occurrences considerably promote rise in the production of greenhouse gas (carbon dioxide) emission levels and coal ash from thermal power plant disposal, both are environmentally hazardous. Coal-fired power plants produce industrial by-products, such as coal-bottom ash (CBA), which has good pozzolanic properties and can be used as cement substitute to improve the quality of CBA as a pozzolanic material. The aim of this research is to examine the impacts of different particle sizes on the effective use of CBA as a cementitious substance to improve pozzolanic reactivity. CBA was collected from Tanjung Bin, sieved through various screen diameters, and then ground until 95 ± 1% of the particles met the ASTM C618 requirement of 45 µm for classification as pozzolanic substances. To evaluate the pozzolanic reaction of CBA based on the strength activity index (SAI), CBA was ground to same fineness as cement. Five substitution levels were used. To obtain SAI data, 10, 20, 30, 40, and 50% cement were partially substituted. The results showed that all the milled CBA samples exhibited pozzolanic characteristics and that the compressive strength of the milled CBA mortar improved with the curing age up to 20% substitution. The successful utilize of CBA as a pozzolanic materials and partial replacement for cement.